Allocation of Fire Detector in Most Economical Way - Tan , Fang Yee (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
In oil and gas industry, fire outbreak is one of the main accidents happened in onshore and offshore plant. Hence, a well-designed fire detection system that offer an adequate coverage on the plant is crucial to safeguard the hazardous area and reduce the damage that caused by fire accident. Most of the modern day detector monitoring system uses visual detector as it provides superior advantage over other conventional detector, such as immunity against dust, reflection and flares. In real life situation, the placement of fire detector in some plant is being done manually by engineers and this might left out certain hazardous area and cause the plant to be on risk. Service to evaluate the effectiveness of fire detector placement is offered by certain professional companies such as Micropack yet they are very costly. Besides, idea to implement the assessment after placement might result in the redundant use of detector, which is unadvisable from the economy perspective. The aim of this project is to offer a simple assessment method that met the possible balance between safety and economy. This could be achieved by identify the best placement of detectors with optimum coverage, which minimum number of detector will be required. A methodology named detector mapping assessment is being introduced to determine the degree of fire detector coverage with respect to the given hazardous grade map.